Alcoholysis of Nyamplung Seed Oil Using Potassium Carbonate Catalyst - Sofiyah, Sofiyah (ASEAN Journal of Chemical Engineering, 2006)
The production of glycerol and ester by alcoholysis of vegetable oils has been widely studied. Various catalysts, such as sodium and potassium hydroxide and sulfuric acid have been used to increase the rate of reaction. This preliminary research studied the possibility of using potassium carbonate catalyst. The experiment was conducted in an autoclave. A certain amount of nyamplung seed oil was poured into the autoclave and then the heater was switched on to heat up the oil to the required temperature of reaction. Besides, a mixture of ethanol and potassium carbonate was heated in a flask equipped with condenser to form ethanolate. As soon as the required temperature was reached, the ethanolate was quickly put into the autoclave containing the nyamplung seed oil. The temperature of the reaction was kept constant for a period of time. At the end of each process, a sample was withdrawn and analyzed for its glycerine content by acetin method. The variables studied were reaction time and catalyst concentration. The experimental data were evaluated by applying pseudo homogeneous approach. It was found that data were in good agreement with first order reaction with respect to nyamplung seed oil. Using an equivalent ratio of 5.1 ethanol to nyamplung seed oil, a temperature of lOOoC,and an agitation speed of 150 rpm, the favorable catalyst concentration was found to be at 0.008 gram of potassium carbonate per gram of nyamplung seed oil. Under this condition, the glyceride conversion was 0.5159 in 75 min.